The photon time delay in magnetized medium magnetosphere. Issue 1 (1st February 2021) - Jorge, Adrián William Romero; Rodríguez Querts, Elizabeth; Pérez Martínez, Aurora; Pérez Rojas, Hugo
Abstract: We calculate the time delay for photons propagating in a charged electron‐positron gas at finite temperature and in an external magnetic field with the final aim of studying the effect for photons in a neutron star magnetosphere. The dispersion relations are solved in terms of analytic functions, in the degenerate, strong magnetic field, and ultra‐relativistic limit. For fixed values of frequency, temperature, and chemical potential, we study the dependence of photon time delay with the magnetic field strength, as well as with distance. For the latter, we adopt a magnetic dipole configuration and obtain that, according to the expectation, photons of higher energy experience a minor time delay. Obtained results are compared with the previous ones obtained for the photon time delay in vacuum magnetosphere.